A Tracer Bolus Method for Investigating Glutamine Kinetics in Humans - Mori, Maiko (Public Library of Science, 2014)
Glutamine transport between tissues is important for the outcome of critically ill patients. Investigation of glutamine kinetics is, therefore, necessary to understand glutamine metabolism in these patients in order to improve future intervention studies. Endogenous glutamine production can be measured by continuous infusion of a glutamine tracer, which necessitates a minimum measurement time period. In order to reduce this problem, we used and validated a tracer bolus injection method. Furthermore, this method was used to measure the glutamine production in healthy volunteers in the post-absorptive state, with extra alanine and with glutamine supplementation and parenteral nutrition. Healthy volunteers received a bolus injection of [1-(13)C] glutamine, and blood was collected from the radial artery to measure tracer enrichment over 90 minutes. Endogenous rate of appearance (endoR(a)) of glutamine was calculated from the enrichment decay curve and corrected for the extra glutamine supplementation. The glutamine endoR(a) of healthy volunteers was 6.1±0.9 µmol/kg/min in the post-absorptive state, 6.9±1.0 µmol/kg/min with extra alanyl-glutamine (p = 0.29 versus control), 6.1±0.4 µmol/kg/min with extra alanine only (p = 0.32 versus control), and 7.5±0.9 µmol/kg/min with extra alanyl-glutamine and parenteral nutrition (p = 0.049 versus control). In conclusion, a tracer bolus injection method to measure glutamine endoR(a) showed good reproducibility and small variation at baseline as well as during parenteral nutrition. Additionally, we showed that parenteral nutrition including alanyl-glutamine increased glutamine endoR(a) in healthy volunteers, which was not attributable to the alanine part of the dipeptide.